Cerebral autoregulation is heterogeneous in different stroke mechanism of ischemic stroke caused by intracranial atherosclerotic stenosis. Issue 1 (23rd October 2020) - Tian, Ge; Ji, Zhong; Lin, Zhenzhou; Pan, Suyue; Yin, Jia
Abstract: Background and Purpose: Intracranial atherosclerotic stenosis (ICAS) is the most common cause of ischemic stroke (IS) and is associated with stroke recurrence. It results in IS due to a variety of mechanisms. However, the influence of brain reserve mechanism on different stroke mechanism is still unclear. Cerebral autoregulation (CA) is an important brain reserve mechanism and is impaired after IS. This study aimed to explore the impaired pattern of CA and assess the association between CA and stroke risk factors in different stroke mechanism caused by ICAS. Methods: IS patients with ICAS (50%–99% stenosis/occlusion) in middle cerebral artery (MCA) or internal carotid artery were enrolled to receive CA examinations within 7 days after onset. Healthy volunteers were also recruited as controls. CA was recorded from spontaneous fluctuations of blood pressure and MCA flow velocity. Transfer function analysis was used to derive CA parameters, including phase difference (PD) and coherence in the low‐frequency range (0.06–0.12 Hz). Results: A total of 89 IS patients and 90 healthy controls were included. Compared with controls, CA was impaired ipsilaterally in patients with parent artery atherosclerosis occluding penetrating artery (POPA) while CA was bilaterally impaired in other stroke mechanisms. And CA on ipsilateral hemisphere was correlated with hypertension/hyperlipidemia in patients with POPA ( r  = −0.481, p  = .008; r  = −0.484, p  = .008). While CA on ipsilateral hemisphere was correlated with perfusion parameter including the arterial spin‐labeling (ASL) parameter cerebral blood flow (CBF) ( r  = 0.893, p  = .007) and collateral circulation status the American Society of Interventional and Therapeutic Neuroradiology/Society of Interventional Radiology (ASITN/SIR) ( r  = 0.610, p  = .021) in patients with hypoperfusion mechanism. Conclusion: In IS patients, CA was impaired heterogeneously and was correlated with different risk factors in varied stroke mechanism. CA can be as an informative determinant of stroke risk in patients with ICAS and to help improving individualized treatment strategies in the presence of ischemic stroke caused by ICAS. Abstract : Currently, there still exists debates on impairment pattern of cerebral autoregulation (CA) in patients with intracranial atherosclerotic stenosis (ICAS). Our study found that CA was impaired ipsilaterally in patients with parent artery atherosclerosis occluding penetrating artery (POPA) while CA was bilaterally impaired in other stroke mechanisms. And CA on ipsilateral hemisphere was correlated with hypertension/hyperlipidemia in patients with POPA, while CA on ipsilateral hemisphere was correlated with perfusion parameter and collateral circulation status in patients with hypoperfusion mechanism. The finding may suggested that CA can be as an informative determinant of stroke risk in patients with ICAS and to help improving individualized treatment strategies in the presence of ischemic stroke caused by ICAS.